O processo de formação do Arquivo da Marinha do Brasil como instituição de pesquisa histórica e militar (1907-1953) - Alessandra Reitz (Navigator)
This is an analysis on the formation process of the Brazilian Naval Archives as a research institution and its contribution for the development of historical and military studies; emphasizing its transformation as a significant place for the Brazilian naval memory.